Harutyun Martirosyan - Bobokhyan, Arsen (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
In the 1920s a new phase began in the history of Armenian archaeology. The lasting peace established in Armenia after a long period of war and unrest fostered the establishment of scientific institutions, museums and other cultural and educational organisations. Nevertheless, the accumulation of archaeological information in 1920s and 1930s had a preliminary character. Armenian scholars collected data from various regions of Armenia without any formal classification. There was no holistic periodisation or chronology of the ancient cultures of the region. In 1959 the Institute of Archaeology and Ethnography was organised in order to change this situation. Harutyun Martirosyan became a member of the Institute and since then he dedicated his scientific activities to solving the essential problems of Armenian archaeology.